User Interface Modelling for SIBI (Sistem Isyarat Bahasa Indonesia/Indonesian Sign Language System) learning applications using the User-Centered Design Method - Ridzky, Desanty; Effendy, Veronikha; Junaedi, Danang (Journal of physics. Conference series, 2019)
Sign Language is a type of language used to help deaf children to communicate. The Indonesian government has created their standardization system for sign language called SIBI (Sistem Isyarat Bahasa Indonesia). Deaf children have characteristics such as lack of memory ability. Therefore they need media for repetition in learning. The actual mobile-based learning could support recurrence in the subject is already available, but not all the designs on mobile technology are suitable for children's needs, proven by testing the existing application using USE Questionnaire which obtained a usability average of 58%, which mean that the app could not provide convenience and satisfaction for users. Therefore, to create a user interface that suits the needs of the user, the User-Centered Design (UCD) method is used. The usability testing conducted for the prototype application and the result is 90% with an excellent category. If the result of the usability is an excellent value, then the app could be used very easy and satisfied for user.